The Level of Nutritional Knowledge of Taekwondo Athletes at GTC Dojang, Semarang City - Naufal Ammar; Agus Darmawan (Universitas Negeri Semarang, 2025)
The background of the problem in this study stems from the fact that although there is awareness about the importance of nutrition in sports, many athletes still lack understanding of basic nutrition principles and how to apply them in daily life. This research aimed to assess the level of nutritional knowledge among Taekwondo athletes at Dojang GTC in Semarang City. This study employed a quantitative descriptive research design aimed at measuring the level of nutritional knowledge among Taekwondo athletes at Dojang GTC in Semarang City. The findings showed that most athletes possessed moderate to good understanding of basic sports nutrition concepts, such as the role of macronutrients, the importance of hydration, and recovery after training. However, a significant proportion of athletes still demonstrated low levels of nutritional knowledge. This highlights the need for structured and continuous nutrition education. Such education is essential not only to raise awareness about the role of nutrition in performance and recovery but also as a preventive measure against fatigue, injury, and reduced physical endurance. This knowledge gap also reflects the limited access to valid nutritional information and the minimal involvement of professional nutritionists in the coaching process at the dojang level. Therefore, interventions in the form of training, counseling, or guided meal planning are urgently needed to ensure that all athletes are equipped with adequate knowledge to support their athletic performance optimally.